Pycnogonida collection of the Shirshov Institute of Oceanology, Russian Academy of Sciences - Zoya Dudnik; Antonina Kremenetskaia (Biodiversity Data Journal)
This dataset comprises detailed information on 2,134 Pycnogonida specimens stored in the Ocean Benthic Fauna collection (collection code: OBFc) of the Shirshov Institute of Oceanology (IORAS). These specimens were collected over a span of 77 years, since 1947, from 996 distinct localities across various regions of the World Ocean.The IORAS Pycnogonida collection stands out for its wide range of Pycnogonida species, including both common and exceptionally rare specimens, some of which are unique to this collection. This diversity makes the dataset an invaluable resource for taxonomists, ecologists and marine biologists, particularly those studying sea spiders. By providing comprehensive data on species distribution and diversity, the collection plays a key role in advancing our understanding of these intriguing marine arthropods. It serves as a vital reference for scientific research, aiding in species identification, the study of ecological relationships and the analysis of biogeographic patterns worldwide.The whole Pycnogonida collection of the Shirshov Institute of Oceanology has undergone a meticulous revision and digitisation process to compile a comprehensive dataset on the geographic, bathymetric and taxonomic specimen distribution. This effort includes the documentation and imaging of the type collection as well as of rare and unique records. The resulting dataset serves as a valuable resource for a variety of scientific disciplines, including taxonomic studies, biodiversity research and biogeographic analyses. This dataset contributes to our understanding of marine biodiversity and the distribution patterns of Pycnogonida across different oceanic regions and depths.